UPAYA PENINGKATAN PEMBELAJARAN TOLAK PELURU DENGAN PENDEKATAN PERMAINAN SIRKUIT PADA KELAS V SEKOLAH DASAR NEGERI 1 ROWOSAR KECAMATAN ROWOSARI KABUPATEN KENDAL TAHUN 2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to determine the increase in student learning outcomes in learning through play shot-put circuit in fifth grade Elementary School District 1 Rowosari Rowosari Kendal District . This study uses action research . The subjects were students of class V Rowosari Elementary School District . Rowosari Kab . Kendal . Techniques of data collection using the test methods , methods of documentation , and questionnaires . The results of this study are based on survey data . Student learning outcomes in the first cycle and the second cycle of action . In the first cycle, the percentage of the total acquisition of the learning achievement of 64% and this achievement is increased by 21 % to 85 % . Increasing the learning process would logically lead to greater student achievement, which in this context is the increasing ability of students to reject bullets . Conclusions of research is learning through play circuits can improve learning outcomes Elementary School fifth grade students of the District 1 Rowosari Rowosari Kendal in the Academic Year 2012/2013 . Research suggestions include a few things , namely : 1 ) The game can be an alternative circuit for teachers Penjasorkes to apply the material in Shot Put , 2 ) Teacher Penjasorkes to improve competence in designing , preparing , implementing and evaluating learning through a variety of sources Â